Feasibility and outcome of the Rotapro system in treating severely calcified coronary lesions: the Rotapro study - Ayoub, Mohamed; Tajti, Peter; Ferenc, Miroslaw; Akın, Ibrahim; Behnes, Michael; Neumann, Franz-Josef; Mashayekhi, Kambis (Cardiology journal, 2023)
Background: The Rotapro study was conducted to evaluate the safety and feasibility of the new Rotapro rotational atherectomy system (RAS) for lesion preparation in calcified coronary artery stenosis. Methods: Between 2015 and 2019 consecutive patients undergoing rotational atherectomy (RA) with the new Rotapro system and the conventional rotablator (Rotablator) were included from the Bad Krozingen Rotablation Registry. The primary endpoint was the incidence of in-hospital major adverse cardiovascular and cerebral event (MACCE) rate. Results: Rotablation was performed in 3.6% of all patients (n = 597) treated by percutaneous coronary intervention. Procedural outcomes were compared according to the applied RAS (n = 246 Rotapro vs. n = 351 Rotablator). Overall technical success was achieved in 98.3% of patients. The primary endpoint of in-hospital MACCE was comparable between the Rotapro- and the Rotablator-group (3.7% vs. 5.7%, respectively, p = 0.254). The Rotapro group was associated with significant reductions of fluoroscopy time (30 vs. 38 min, p < 0.0001), procedural time (82.5 vs. 96 min, p = 0.0003), applied contrast volume (210 vs. 290 mL, p < 0.0001) and radiation dose (6129 vs. 9827 cGy*cm2, p < 0.0001) compared to the Rotablator group. Conclusions: The present study demonstrates the safety and efficacy of the new Rotapro system. Inhospital MACCE rates were comparable between both RAS, whereas Rotapro was associated with less fluoroscopy time, radiation dose as well as contrast use.